Blood–brain barrier breakdown, central nervous system cell damage, and infiltrated T cells as major adverse effects in CAR-T-related deaths: a literature review - Del Duca, Fabio; Napoletano, Gabriele; Volonnino, Gianpietro; Maiese, Aniello; La Russa, Raffaele; Di Paolo, Marco; De Matteis, Serena; Frati, Paola; Bonafè, Massimiliano; Fineschi, Vittorio (Frontiers in Medicine, 2024)
Background CAR-T-related deaths observed worldwide are rare. The underlying pathogenetic mechanisms are the subject of study, as are the findings that enable diagnosis. A systematic literature search of the PubMed database and a critical review of the collected studies were conducted from the inception of this database until January 2023. The aim of the study is to determine when death is related to CAR-T cell therapy and to develop a shareable diagnostic algorithm. Methods The database was searched by combining and meshing the terms (“CAR-t” OR “CART”) AND (“Pathology” OR “Histology” OR “Histological” OR “Autopsy”) AND (“Heart” OR “Cardiac” OR “Nervous System” OR “Kidney” OR “Liver”) with 34 results and also the terms: [(Lethal effect) OR (Death)] AND (CAR-T therapy) with 52 results in titles, abstracts, and keywords [all fields]. One hundred scientific articles were examined, 14 of which were additional records identified through other sources. Fifteen records were included in the review. Results Neuronal death, neuronal edema, perivascular edema, perivascular and intraparenchymal hemorrhagic extravasation, as well as perivascular plasmatodendrosis, have been observed in cases with fatal cerebral edema. A cross-reactivity of CAR-T cells in cases of fatal encephalopathy can be hypothesized when, in addition to the increased vascular permeability, there is also a perivascular lymphocyte infiltrate, which appears to be a common factor among most authors. Conclusion Most CAR-T-related deaths are associated with blood–brain barrier breakdown, central nervous system cell damage, and infiltrated T cells. Further autopsies and microscopic investigations would shed more light on the lethal toxicity related to CAR-T cells. A differential diagnosis of CAR-T-related death is crucial to identifying adverse events. In this article, we propose an algorithm that could facilitate the comparison of findings through a systematic approach. Despite toxicity cases, CAR-T therapy continues to stand out as the most innovative treatment within the field of oncology, and emerging strategies hold the promise of delivering safer therapies in future.